Clinical characteristics and genotype-phenotype correlation analysis of familial Alzheimer’s disease patients with pathogenic/likely pathogenic amyloid protein precursor mutations - Liu, Yingzi; Xiao, Xuewen; Liu, Hui; Liao, Xinxin; Zhou, Yafang; Weng, Ling; Zhou, Lu; Liu, Xixi; Bi, Xiang-yun; Xu, Tianyan; Zhu, Yuan; Yang, Qijie; et al. (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is a progressive neurodegenerative disease associated with aging, environmental and genetic fac-tors. APP is a known pathogenic gene for familial AD (FAD), accounting for about 1% of FAD. Currently, more than 70 APP mutations have been reported, but the genotype-phenotype correlation remains unclear. In this study, we collected clinical data from patients carrying APP mutations defined as pathogenic/likely pathogenic according to the ACMG guide-lines. Then we reanalyzed the clinical charac-teristics and identified genotype-phenotype correlations in APP mutations. Our results indicated that the clinical phenotypes of APP mutations are generally consistent with typical AD despite some specific and heterogeneous features. We also found some differences in V717I mutation compared to other APP muta-tions, and individuals with extrapyramidal symptoms (EPS) or ataxia were more likely to have spastic par-aplegia.